Early Manifestations of Acute Renal Failure in a Pregnant Woman with Diabetes - Behjat Khorsandi; Mahsa Khoshnam Rad; Maryam Moradi; Fatemeh Mohammadnejad (Golestan University Of Medical Sciences, 2020)
Background: Diabetes is a major risk factor for acute renal failure, which is commonly seen during pregnancy. Patients with kidney failure are at significant risk for adverse pregnancy outcomes, and pregnancy may accelerate the progression of kidney disease in these patients. We herein report a pregnant woman with early manifestations of kidney failure during pregnancy. Case description: The patient was a 39-year-old G2P1L1 woman with a gestational age of 14 weeks and 4 days who presented with edema and hypoglycemia. The patient had overt pre-orbital edema and less severe generalized edema. Finally, due to the patientchr('39')s conditions based on diabetes mellitus under insulin therapy, edema, proteinuria and high creatinine level (1.5 mg/dl) in the past two weeks, pregnancy was terminated as recommended by the medical commission and after obtaining informed consent from the patient. Conclusion: Diabetes is an important risk factor for acute renal failure. Women with kidney failure are more likely to experience adverse pregnancy outcomes. Diabetic women who consider becoming pregnant should be first evaluated by a gynecologist and nephrologist and receive specialized advice. Given the complexity of care in affected women, a multidisciplinary approach is needed to achieve the best pregnancy outcome.